A Review on the Design and Characteristics of English Language Learning and Teaching in a Standard-Based Curriculum: Kurikulum Merdeka - Muhamad Aziz Muslim; Sri Sumarni (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
The research is meant to conduct a review of the design of Kurikulum Merdeka and to reveal the characteristics of the teaching and learning of English based on this curriculum. The descriptive qualitative method was employed in this review. Major designs of language curriculum offered by scholars were identified, analyzed, and synthesized to set the rubrics for analyzing the Kurikulum Merdeka. The Kurikulum Merdeka document especially the introduction part in the learning outcome statements was analyzed based on the rubrics to reveal its design and the teaching and learning characteristics. The analysis of the major English language curriculum design, the pertinent characteristics of the major English language curriculum design, the description of the design of the English language curriculum in Kurikulum Merdeka, and the characteristics of the teaching and learning English based on Kurikulum Merdeka are presented as the result of the research.